2015
DOI: 10.1007/s11746-015-2606-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Oxidation Analysis of Forage Turnip (Raphanus sativus L. var. oleiferus Metzg.) Oil

Abstract: The seed of the R. sativus L. has around 40-54 % of its weight in oil, extracted by mechanical pressing. The resulting cake retains around 7.5 % of its own weight in oil and has a high nutritional value, in addition to high palatability as cattle feed [1].It is known, however, that lipids can undergo chemical changes during storage and/or processing, such as hydrolytic rancidity and oxidative rancidity, compromising the quality of the oil [3]. These oxidative processes constitute one of the most important tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
(39 reference statements)
2
11
0
2
Order By: Relevance
“…As observed, the peak at 232 nm grows as a function of exposure area, whereas the peak at 270 nm increases slightly with the exposure area. This result indicates that an increase in conjugated dienes, as a result of degradation of unsaturated mono-alkyl esters, 24 confirms higher levels of oxidation with increased exposure area. Accordingly, the accelerated oxidation test achieves the objective and provides different oxidation states.…”
Section: Uv-vis Spectroscopymentioning
confidence: 64%
“…As observed, the peak at 232 nm grows as a function of exposure area, whereas the peak at 270 nm increases slightly with the exposure area. This result indicates that an increase in conjugated dienes, as a result of degradation of unsaturated mono-alkyl esters, 24 confirms higher levels of oxidation with increased exposure area. Accordingly, the accelerated oxidation test achieves the objective and provides different oxidation states.…”
Section: Uv-vis Spectroscopymentioning
confidence: 64%
“…The oil of both species is rich in erucic acid, which is not suitable for use in food applications but important as industrial crops to produce lubricants, polymers, pharmaceuticals items (Lalas et al, 2012;Chammoun et al, 2013) and biodiesel (Wazilewski et al, 2013). The biodiesel produced of the crambe and turnip forage oils have higher composition of fatty acids and fatty alcohols which confer a higher oxidative stability (Oliveira et al, 2015;Zhu et al, 2016) and a similar energetic conversion, compared to soybean oil (Wazilewski et al, 2013), demonstrating its great potential for biodiesel feedstock production. In addition, the use of vegetable oils instead of diesel is of great environmental importance for ensuring power generation with reduced gas emission (Rosa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, R. sativus and C. abyssinica are winter crops and can be cultivated in the off-season of soybean and corn crops (Carlsson et al, 2014;Oliveira et al, 2015), which corresponds to the dry period. The frequent exposure to water deficits compromises the growth and development of plants and, consecutively, the crop production (Liu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous works have shown that the acidification of vegetable oils reflects on the changes in the absorbances at 232 and 270 nm with direct impact on the emission profile [ 15 , 16 ]. However, the optical behavior is still not completely understood for biodiesel, especially for unconventional vegetable sources studied here (from Raphanus sativus L. and Sesamum indicum L. seeds).…”
Section: Introductionmentioning
confidence: 99%